2005
DOI: 10.1073/pnas.0503527102
|View full text |Cite
|
Sign up to set email alerts
|

Electrically monitoring DNA repair by photolyase

Abstract: Cyclobutane pyrimidine dimers are the major DNA photoproducts produced upon exposure to UV radiation. If left unrepaired, these lesions can lead to replication errors, mutation, and cell death. Photolyase is a light-activated flavoenzyme that binds to pyrimidine dimers in DNA and repairs them in a reaction triggered by electron transfer from the photoexcited flavin cofactor to the dimer. Using gold electrodes modified with DNA duplexes containing a cyclobutane thymine dimer (T<>T), here we probe the electroche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
82
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 39 publications
2
82
0
Order By: Relevance
“…Both methylene blue and ruthenium hexammine bind to the DNA monolayer, yet while methylene blue is known as a redox active intercalator that shows electrochemical activity only as long as individual duplexes forming a DNA monolayer are completely Watson-Crick base paired (2), the ruthenium hexamine is electrostatically attached to the DNA phosphate groups, thus its electrochemistry is insensitive to the base-stacking perturbations within the DNA film (19,20). In our approach, shown schematically in figure 1, a redox mediator, Fe(CN) 6 4-is first oxidized at the SECM tip microelectrode (Pt disk) resulting in a steady-state current due to the hemispherical diffusion of Fe(CN) 6 4-to the tip (21). Subsequently, the SECM tip is lowered proximal to the surface of the electrochemically polarized Au electrode modified with a monolayer of ds-DNA containing either ruthenium hexammine (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Both methylene blue and ruthenium hexammine bind to the DNA monolayer, yet while methylene blue is known as a redox active intercalator that shows electrochemical activity only as long as individual duplexes forming a DNA monolayer are completely Watson-Crick base paired (2), the ruthenium hexamine is electrostatically attached to the DNA phosphate groups, thus its electrochemistry is insensitive to the base-stacking perturbations within the DNA film (19,20). In our approach, shown schematically in figure 1, a redox mediator, Fe(CN) 6 4-is first oxidized at the SECM tip microelectrode (Pt disk) resulting in a steady-state current due to the hemispherical diffusion of Fe(CN) 6 4-to the tip (21). Subsequently, the SECM tip is lowered proximal to the surface of the electrochemically polarized Au electrode modified with a monolayer of ds-DNA containing either ruthenium hexammine (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This long-range electron transfer is possible within a distance of 10-25Å in biological redox reactions (16). It has been proposed that some repair enzymes use electron transfer from redox cofactors to allow the detection of DNA lesions generated by the oxidation at remote site (17)(18)(19). However, it was also observed that EET can go through without redox cofactors as evidenced in the case of Escherichia coli DNA photolyase that can repair thymine dimers without the aid of redox cofactors (20,21).…”
Section: Introductionmentioning
confidence: 95%
“…Self-assembled DNA monolayers (Davis and Higson, 2005;Finot et al, 2003;Gooding et al, 2003;Legay et al, 2005;Love et al, 2005) provide attractive platforms for electrical monitoring of DNA-protein interactions (Anne et al, 2007;Boon et al, 2002;DeRosa et al, 2005;Drummond et al, 2003;Gorodetsky et al, 2006;Hianik et al, 2004Hianik et al, , 2005Li et al, 2004;Wang, 2002). A convenient way to obtain DNA films is the immobilization of thiolated modified DNA strands on a gold surface (Chaki and Vijayamohanan, 2002;Davis and Higson, 2005;Herne and Tarlov, 1997;Legay et al, 2007;Love et al, 2005) due to the strong affinity of sulfur compounds for gold (Meunier-Prest et al, 2010).…”
Section: Introductionmentioning
confidence: 97%